2015
DOI: 10.4239/wjd.v6.i2.321
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic glycogenosis: An underdiagnosed complication of diabetes mellitus?

Abstract: Hepatic glycogenosis (HG) is characterized by excessive glycogen accumulation in hepatocytes and represents a hepatic complication of diabetes that particularly occurs in patients with longstanding poorly controlled type 1 diabetes (T1D). HG has been reported to be a very rare disease, although it is believed to be extremely underdiagnosed because it is not possible to distinguish it from non-alcoholic fatty liver disease (NAFLD) unless a liver biopsy is performed. In contrast to HG, NAFLD is characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…In some cases, this can lead to a glycogen overload, resulting in liver damage. Hepatic glycogenosis or hepatomegaly is a glycogen overload disorder [58]. Repeated ketoacidosis episodes accompanied by high blood glucose levels increase the risk of glycogen overload in the liver, as DKA is often treated with insulin administration.…”
Section: Dka Oxidative Stress and Diabetic Co-morbiditiesmentioning
confidence: 99%
“…In some cases, this can lead to a glycogen overload, resulting in liver damage. Hepatic glycogenosis or hepatomegaly is a glycogen overload disorder [58]. Repeated ketoacidosis episodes accompanied by high blood glucose levels increase the risk of glycogen overload in the liver, as DKA is often treated with insulin administration.…”
Section: Dka Oxidative Stress and Diabetic Co-morbiditiesmentioning
confidence: 99%
“…GS activity often becomes dysregulated in steatosis, exacerbating the already existing dysglycemia (12,17,18). Recent reports have shown that hepatic overexpression of the G-regulatory subunits of PP1 increased hepatic glycogen accumulation, protected mice from fasting hypoglycemia, and accelerated postprandial blood glucose clearance in mice fed a chow diet or an HFD or in rats with streptozotocininduced diabetes (15,19,20).…”
mentioning
confidence: 99%
“…However, the key clinical features are hepatomegaly and a mild to moderate increase in transaminases, although in some cases, the transaminase levels can be dramatically elevated, up to 30 times the upper limit of normal (10). As in case 3, and in to a lesser extends in case 2, very high transaminase levels in the range of acute hepatitis has been reported in patients with GH (4,11).…”
Section: Discussionmentioning
confidence: 98%